Factors associated with the level of compliance of nurses in universal precaution application - Sofiana, Liena; Ayu, Suci Musvita; Sundari, Dewik (International Journal Of Community Medicine And Public Health, 2019)
Background: The highest prevalence of surgical wound infections in NurHidayah Hospital occurred in 2014 which is at 2.80%. This was because nurses’ compliance in using PPE and hand washing was still low and the culture for reporting needle puncture events had not been implemented so that the number of nurses who were punctured was still unknown. Meanwhile, the lowest prevalence of surgical wound infections occurred in 2016 amounting to 0.76%, this happened because the compliance of nurses in using PPE was quite high and the incidence of needle puncture reached 0 (zero) but compliance in hand washing was still low. Methods: This study was a quantitative study with an observational analytic method with a cross sectional design. The variables in this study were knowledge, attitudes, working period, training and nurse compliance in the application of universal precaution with the number of respondents 46 nurses. The research instruments used were questionnaires and observation sheets. The data analysis was conducted using chi square test and fisher test. Results: Factor associated with the level of nurse compliance in universal university application was attitudes (0.000), while factors not related to the level of nurse compliance in the application of universal precaution include knowledge (0.124), years of service (0.657) and training (0.098). Conclusions: There is a relationship between attitudes and levels of nurse compliance in implementing universal precaution in NurHidayah Hospital. There is no relationship between knowledge, work and training with the level of nurse compliance in the application of universal precaution at NurHidayah Hospital.